Assessment of quality of essential medicines in public health care facilities of Nepal: Findings of nationwide study - Neelam Dhakal; Pradip Gyanwali; Baburam Humagain; Rajendra BC; Nisha Jha; Phoolgen Sah; Amita Pradhan; Meghnath Dhimal; Anjani Kumar Jha (PLOS Global Public Health, 2023)
Essential medicines are those medicines that satisfy the primary health care needs of the citizens. Poor quality of essential medicines can have serious impact on public health. Thus, this study is aimed to assess the quality of essential medicines available in public health care facilities of Nepal. A cross sectional descriptive study was carried out in 62 health facilities across 21 districts, representing all seven provinces of Nepal and selected proportionately from all three ecological regions i.e. Terai, Hill and Mountain using lottery method. Health facilities in selected districts were chosen using random number generator. Face to face interview was taken with health facility in charge using structured questionnaire. All storage conditions information was recorded through observation checklists. Temperature and humidity were measured using a digital instrument. Similarly, 20 different generic medicines were collected for quality testing. The obtained data were entered in Epidata version 3.1, cleaned in Microsoft Excel 2007 and analyzed in SPSS version 16.0. Among 62 health facilities, only 13% of health facilities were found to follow the medicine storage guidelines, with temperature and humidity levels exceeding recommended limits. Out of 244 batches of 20 different generics of essential medicines, 37 batches were found to be substandard. These substandard medicines were- Ciprofloxacin hydrochloride eye/ear drop, Iron supplement tablets, Metformin Hydrochloric tablet, Metronidazole Tablets, Paracetamol Oral suspension, Paracetamol tablet and Povidone Iodine solution. The study recommends the urgent need for the Government of Nepal to prioritize ensuring the quality of essential medicines in the country.